Risks of Solely Relying on VS30 in Ground Motion Response Studies - Amin Ghanbari; Younes Daghigh; Forough Hassanvand (Salehan Institute of Higher Education, 2018)
The average shear wave velocity of the uppermost 30 m of earth (Vs30) is widely used in seismic geotechnical engineering and soil-structure interaction studies. In this regard, any given subsurface profile is assigned to a specific site class according to its average shear wave velocity. However, in a real-world scenario, entirely different velocity models could be considered in the same class type due to their identical average velocities. The objective of the present study is to underline some of the risks associated with solely using Vs30 as a classification tool. To do so, three imaginary soil profiles that are quite different in nature, but all with the same average Vs were considered and were subjected to the same earthquake excitation. Seismic records acquired at the ground surface demonstrated that the three sites have different ground motion amplifications. Then, the different ground responses were used to excite a five-story structure. Results confirmed that even sites from the same class can indeed exhibit different responses under identical seismic excitations. Our results demonstrated that caution should be practiced when large-contrast velocity models are involved as such profiles are prone to pronounced ground motion amplification. This study, which serves as link between soil dynamics and structural dynamics, warns practitioners about the risks associated with oversimplifying the subsurface profile. Such oversimplifications can potentially undermine the safety of existing or future structures.